030 Do we investigate women equally compared with men in a DGH RACPC?. (22nd September 2015) - Carter, S E; Lloyd, G; Patel, N R; Taggu, W; Rayasam, R
Abstract : Women develop coronary heart disease approximately 10 years later than men. Significant bias against women in the use of investigations for stable angina has been observed, also women with confirmed coronary heart disease are less likely to undergo revascularisation. Objective: To evaluate whether women are investigated equally to men at a RACPC. Methods: The structure, process and outcome of the Rapid Access Chest Pain Service of a typical district general hospital (DGH), involving quantitative and qualitative methodology. Quantitative evaluation of age, risk factors, equity to exercise testing, MIBI scans, stress echocardiogram, coronary angiography and revascularisation procedures in women were compared with men. Qualitative data on the ideas and opinions of medical staff working within a district general hospital setting was collected on the subject of whether women need to be evaluated differently from men. Results: Three hundred and seventy patients were included (183 women vs 187 men). Women were older 61.5 vs 57 years (p=0.003, CI −1.4 to –6.8), had lower 10 year CHD risk scores 7% vs 13.9% (p=0.001, CI 5.3 to 8.1), less women 91% vs than men 97% were able to exercise test (p=0.02), but overall there was no difference between the genders for having a primary test of either ETT (94%), direct MIBI scan (0.6%), stress echo(0.3%) or direct angiography(3%) or no test (2%) (p=0.49). Equal men (n=67) to women (n=65) underwent angiography, but significantly more men than women (42 vs 22) (p=0.008) had a significant stenosis on angiogram and more women had a totally normal angiogram (14 vs 30) (p=0.008). More men (24.6%) than the women (13.7%) had an event or diagnosis of CAD defined as MI, PCI, CABG, CA >50% stenosis, or all cause death (p=0.008). Group meeting analysis highlighted: 1. The exercise test had a high negative predictive value in men and women. 2. The exercise test was considered sub-optimal as a triage tool as women had a trend for more false positive results. 3. There was concern that women may have more small vessel or microvascular disease than men that would not be apparent by coronary angiography. 4. Further research study into non-invasive testing in women was required. Conclusion: The RACPC showed no gender bias to undergo a primary investigation. Women were less likely to undergo exercise testing and were more likely to have false positive results. Overall the incidence of coronary disease was lower in women. From the qualitative data there was concern that exercise testing was not the best primary tool to investigate women although it initiates further investigations.